LONGITUDINALLY EXTENSIVE TRANSVERSE MYELITIS: A VARIETY OF CAUSES SEEN WITHIN THE NATIONAL NEUROMYELITIS OPTICA SERVICE. (29th November 2012) - Kitley, J; George, J; Leite, MI; Palace, J
Abstract : Longitudinally extensive transverse myelitis refers to inflammation of the spinal cord causing T2 hyperintensity on spinal MRI that extends over three or more vertebral segments. Although commonly associated with neuromyelitis optica, there are many other causes that should be considered. These include other inflammatory monophasic myelitises, infection, and mimics such as malignancy and spinal cord infarction. We review the diverse causes of longitudinally extensive transverse myelitis, with illustrative cases from the John Radcliffe Hospital, Oxford. We also summarise laboratory and radiological features that can help to differentiate these causes.